Cassava Quality Classification for Tapioca Flour Ingredients by Using ID3 Algorithm - Yohanssen Pratama; Hadi Sutanto Saragi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cassava is one of the main foods consumed by Indonesian people and main ingredients to make tapioca flour. In North Sumatera there is factory that produced tapioca flour to fulfill consumer demand.  To be able to meet the needs of consumers and seize market share, the product must have a good quality. Product specifications are a reference for product quality and measured with 7 parameters. The seven parameters include whiteness, moisture content, spotness, ash content, thinness, residual screen, pH flour, which meets the Indonesian National Standard. In this research we use two parameters (whiteness and spotness) to determine the quality of cassava and help the factory to maintain their product quality. In here we use blob and edge detection method in image processing to detect spot and after that classified the cassava by using an ID3 algorithm.